The effect of (3-aminopropyl) triethoxysilane and curcumin coating on the physicochemistry of Fe 3 O 4 particles as theranostics of oral cancer: qualitative study descriptive - Yohannes, Gabriel; Djustiana, Nina; Mardhian, Deby Fajar; Sukotjo, Cortino; Aripin, Dudi (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Superparamagnetic iron oxide nanoparticles (SPION) has been used in MRI and have the capability to conjugate with different ligands. One of the active ingredients of interest in biomedical application is curcumin (Cur), which has been shown to have anti-inflammatory effect, wound healing property, and anti-cancer activity. However, such conjugation may need to be facilitated by polymer, such as 3-aminopropyltrimethoxysilane (AMPTS). This study aims to describe the effect of coating materials AMPTS and Cur on the physicochemistry of Fe3O4 particles as a diagnostic of oral cancer. Methods: Modified SPIONs were synthesized by a simple coprecipitation method. Fe3O4 particles were characterized using Fourier transform infrared spectroscopy (FTIR) to analyze the conjugation yield. Next, modified SPIONs were analyzed using dynamic light scattering (DLS) to examine size distribution. Furthermore, zeta potential of the particles was examined. Results: DLS showed size increases after modification of SPION with different materials. In addition, there were slight changes in zeta potential. However, FTIR showed no differences in peaks, indicating that no conjugation was successful. Conclusion: Although FTIR showed no differences in peaks, DLS and zeta potential showed changes with different coatings, which may indicate conjugation. However, further analyses must be carried out to quantify the conjugation yield.KEYWORDS: AMPTS, curcumin, iron oxide, oral cancer, coprecipitationPengaruh bahan pelapis AMPTS dan kurkumin terhadap fisikokimia partikel Fe3O4 sebagai teragnostik kanker mulut: studi deskriptifABSTRAKPendahuluan: Superparamagnetic iron oxide nanoparticle (SPION) telah digunakan dalam MRI dan memiliki kemampuan untuk dikonjugasi dengan berbagai ligan. Salah satu bahan aktif yang menjadi sorotan di bidang biomedis adalah curcumin yang memiliki sifat anti-inflamasi, penyembuhan luka, dan aktivitas anti-kanker. Akan tetapi, konjugasi tersebut biasanya memerlukan fasilitator berupa polimer, seperti 3-aminopropyltrimethoxysilane (AMPTS). Penelitian ini bertujuan untuk mendeskripsikan pengaruh bahan pelapis 3-aminopropyltrimethoxysilane (AMPTS) dan kurkumin (Cur) terhadap fisikokimia partikel Fe3O4 sebagai teragnostik kanker mulut. Metode: SPION disintesis dan dimodifikasi dengan bahan-bahan pelapis tersebut melalui metode kopresipitasi sederhana. Untuk menganalisis hasil konjugasi, sampel dikarakterisasi dengan fourier transform infrared spectroscopy (FTIR). Berikutnya, sampel dianalisis dengan dynamic light scattering (DLS) untuk melihat distribusi ukuran. Kemudian, potensial zeta sampel diukur. Hasil: DLS menunjukkan peningkatan ukuran setelah modifikasi SPION dengan bahan pelapis. Selain itu, ada perubahan dalam potensial zeta. Akan tetapi, analisis FTIR tidak menunjukkan perbedaan puncak serapan yang mengindikasikan ketiadaan konjugasi. Simpulan: Meskipun FTIR tidak menunjukkan perbedaan puncak serapan setiap sampel, DLS dan potensial zeta menunjukkan perubahan nilai untuk setiap sampel dengan coating berbeda, yang boleh jadi mengindikasikan konjugasi. Akan tetapi, analisis lebih lanjut perlu dilakukan untuk mengkuantifikasi konjugasi.KATA KUNCI: AMPTS, kurkumin, besi oksida, kanker mulut, kopresipitasi